(Meth)acrylate liquid crystalline polymers for membrane applications. Issue 43 (3rd August 2015) - Rabie, Feras; Sedlakova, Zdenka; Sheth, Swapnil; Marand, Eva; Martin, Stephen M.; Poláková, Lenka
ABSTRACT Synthesis and characterization of a series of linear copolymers with liquid crystalline side chains is reported. Methacrylate monomers containing cyanobiphenyl as a mesogenic group were prepared. These monomers were then copolymerized with 2‐ethylhexyl acrylate in varying molar ratios. The structure and composition of the monomers and corresponding polymers were determined by 1H‐NMR, elemental analysis and size‐exclusion chromatography. Thermal properties of the polymers were studied using differential scanning calorimetry, polarized optical microscopy, and X‐ray scattering techniques. Increasing mesogen content resulted in an increase of the glass transition temperature of the copolymers. In addition, above a threshold mesogen content the copolymers exhibited smectic mesophases. Using a solution casting technique, a membrane was fabricated to study single gas transport behaviors. Permeabilities, were in the order of CO2 > propylene > O2 > N2 > CH4 > propane. Diffusion coefficients correlated well to Lenard–Jones Diameter. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42694.